THE PROBLEM OF INTERPRETATION OF RULE OF LAW IN VIEW POSITIONS OF HIGHEST JUDICIAL INSTANCES - Anton Viktorovich Pastelnyak (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the problem of interpretation of the rules of law in judicial proceeding, offers to identify legal positions of highest judicial instances as acts of official interpretation of material rules.